vaginal bacterial flora and its antibiogram in bitches with vaginitis in ibadan (2011)
vaginal swab cultures are useful in diagnosing and treating certain diseases of the reproductive tracts. We therefore conducted a study to determine the bacterial flora present in some bitches with vaginitis presented for treatment in a clinic in ibadan. in all, eight of 36 bitches presented during the study period had visible abnormal vaginal discharges ranging from thick to mucoid in consistency and brown to creamy and milky in colour and were selected for the study. vaginal swabs were aseptically obtained and inoculated onto blood and McConkey agar and the plates were incubated at 37 degreeC FOR 24 hours. Gram staining and other routine biochemical tests as well as drug sensitivity tests were further carried out in the identification of the bacterial organisms. our findings showed the presence of Escherichia coli 933.33%), klebsiella spp (33.33%), streptococus pyogenes (20.00%) and staphytococcus aureus (13.33%). the isolated bacteria were, to a very large extent resistant to most of the commonly used antibiotics like tetrecyclin,ampicilin,streptomycin and septin,but highly susceptible to tarivid,ciprotab,augumentin and rocephine. it therefore suffices to say that vaginal bacterial cultures and drug sensitivity tests are sine qua non before initiating any treatment in bitches with vaginitis.